The Impact of COVID-19 on Sleep Quality in People Living With Disabilities - Heinze, Nikki; Hussain, Syeda F.; Castle, Claire L.; Godier-McBard, Lauren R.; Kempapidis, Theofilos; Ftouni, Suzanne; Espie, Colin A.; Gomes, Renata S. M. (Frontiers in Psychology, 2021)
Background: Research exploring the impact of the COVID-19 pandemic on sleep in people with disabilities has been scarce. This study provides a preliminary assessment of sleep in people with disabilities, across two timepoints during the pandemic, with a focus on those with visual impairment (VI). Methods: Two online surveys were conducted between April 2020 and March 2021 to explore sleep quality using the Pittsburgh Sleep Quality Index. A convenience sample of 602 participants completed the first survey and 160 completed the follow-up survey. Results: Across both timepoints, participants with disabilities reported significantly poorer global sleep quality, sleep duration, latency, disturbance and higher use of sleep medication than those with no disabilities. Participants with VI reported significantly higher levels of sleep disturbance and use of sleep medication at both timepoints, poorer global sleep quality, sleep duration and latency at time 1, and daytime dysfunction at time 2, than those with no disabilities. Global sleep quality, sleep duration, sleep efficiency and self-rated sleep quality deteriorated significantly in participants with no disabilities, but daytime dysfunction increased in all three groups. Disability and state anxiety were significant predictors of sleep quality across both surveys. Conclusions: While sleep was consistently poorer in people with disabilities such as VI, it appears that the COVID-19 pandemic has had a greater impact on sleep in people with no disabilities. State anxiety, and to a lesser extent disability, were significant predictors of sleep across both surveys, suggesting the need to address anxiety in interventions targeted towards improving sleep.